Key Competencies for Sustainability in University of Iceland Curriculum - Auður Pálsdóttir; Lára Jóhannsdóttir (Sustainability, 2021)
Sustainable development is growingly being developed in universities around the world. The United Nations presented eight Sustainability Key Competencies (SKCs) that represent cross-cutting competencies crucial to advance sustainable development and achieve Sustainable Development Goals. The aim of this research is to know to what extent the University of Iceland courses seem to include the emphasis of the SKCs, either in the course description text or the learning outcomes. Data collection took place in early 2020 and included analysing every single university’s course description text and learning outcomes using a curriculum analysis key for SKCs. Results show that proportionally, most signs of SKCs were found for SKC 3 (Normative competency) in 53% of courses in the university, and SKC 6 (Critical thinking competency) in 46% of the university’s courses. For individual schools of the university, the far highest proportion of signs of SKC was found for the School of Education (5.0 signs per course) and the relatively fewest for the School of Humanities (1.1 sign per course). The results are discussed both in relation to identified competencies needed for the pressing sustainability problems humanity faces, and in the light of a discrepancy appearing between the university’s ranking according to Times Higher Education University Ranking by citations, research, and teaching, and the proportional signs of individual SKCs within the University of Iceland.